1992
DOI: 10.2307/1542208
|View full text |Cite
|
Sign up to set email alerts
|

Cell Cooperation During Host Defense in the Solitary Tunicate Ciona intestinalis (L)

Abstract: Phagocytosis in the solitary ascidian Ciona intestinalis was investigated using mixed and separated populations of blood cells in vitro. Only the vacuolar and granular amoebocytes were seen to ingest bacteria, and when the serine protease inhibitors, STI, or benzamidine were added to monolayers of mixed cell types, uptake was significantly reduced. Analyses carried out with isolated cells revealed that phagocytosis was enhanced by incubation of the bacteria in blood cell lysate supernatants (CLS) that had been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
1

Year Published

1993
1993
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 27 publications
3
28
1
Order By: Relevance
“…Microscopic observations showed PO activity distributed in the tunic matrix and contained in the large granule of URGs and granules of granulocytes, whereas few morula cells were stained. This finding was in agreement with our previous report on hemocytes (Parrinello et al 2003), whereas Smith and Peddie (1992) proposed that PO activity of HLS might be mainly attributable to morula cells contained in homogenates prepared from a separated hemocyte band in which this cell type was enriched together with vacuolated (compartment) cells. However, no cytochemical assay was carried out, and URGs were not identified in the separated hemocyte bands.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Microscopic observations showed PO activity distributed in the tunic matrix and contained in the large granule of URGs and granules of granulocytes, whereas few morula cells were stained. This finding was in agreement with our previous report on hemocytes (Parrinello et al 2003), whereas Smith and Peddie (1992) proposed that PO activity of HLS might be mainly attributable to morula cells contained in homogenates prepared from a separated hemocyte band in which this cell type was enriched together with vacuolated (compartment) cells. However, no cytochemical assay was carried out, and URGs were not identified in the separated hemocyte bands.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, LPS was an activator, even when used at a concentration lower than that used for activating HLS, and its effect was close to that of trypsin. Similar results have been obtained by assaying HLS (Smith and Söderhäll 1991;Smith and Peddie 1992;Jackson et al 1993), and proPO activation has been reported to be dependent on LPS-activated serine proteases contained in hemocytes. However, our results on the THS are in part conflicting with this pathway.…”
Section: Discussionsupporting
confidence: 84%
“…Tunicate globular granulocytes such as those called elsewhere morula cells, on contact with foreign molecules, can degranulate and release the content of their vacuoles, mainly inactive prophenoloxidase that, once active, produces melanin which accumulates in some areas of the tunic (Ballarin et al, 2001;Cammarata and Parrinello, 2009;Cammarata et al, 2008). Thus, different enzymatically catalysed cascades involved in clotting, melanization, and complement activation (Lavelle et al, 2010;Maldonado-Contreras and McCormick, 2011) can recruit a variety of cell types (Arizza and Parrinello, 2009;Parrinello, 1996;Vizzini et al, 2008) and induce the expression of characteristic innate immune receptors (Dishaw et al, 2011;Parrinello, 2009;Sasaki et al, 2009;Shida et al, 2003) and immunological phenomena (Melillo et al, 2006;Smith and Peddie, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that elimination of chimeric partners involves the integrated function of both homeostatic cell turnover programs with cytolytic activation. Indeed, previous analyses carried out with isolated phagocytic cells revealed that engulfment was enhanced by incubation with cell lysate supernatants made from MCs, but not other cell types, suggesting that opsonins or other prophagocytic factors are derived from MCs and that phagocytosis requires cooperation from other activated cell types (34). These insights raise important questions about whether this strategy for immune elimination may apply to other settings, such as for the elimination of tumors or chronic infections, using compounds that potentiate phagocytosis in combination with agents that promote cytotoxicity.…”
Section: Significancementioning
confidence: 96%